Telling True Stories: A Nonfiction Writers' Guide From the Nieman Foundation at Harvard University - Barbara Rixstine (Journal of Applied Communications, 2007)
A book review of Telling True Stories: A Nonfiction Writers' Guide from the Nieman Foundation at Harvard University, edited by Mark Kramer and Wendy Call.